Anthropometric and Physical Fitness Differences Among Brazilian Adolescents who Practise Different Team Court Sports - Silva, Diego Augusto Santos (Akademia Wychowania Fizycznego w Katowicach, 2013)
The objective of this work was to compare the anthropometric and physical fitness characteristics of Brazilian adolescents who practise team court sports and to compare specific parameters obtained for adolescents with data from the general population. This was a cross-sectional study of 1,348 male adolescents grouped as follows: basketball players (n = 287), indoor soccer players (n = 665), handball players (n = 108) and volleyball players (n = 288), all between 10 and 14 years of age. Anthropometric (body mass, body height, arm span, and body mass index) and physical fitness data (flexibility, muscular strength, explosive power, speed, aerobic fitness and agility) were collected. The Brazilian population was used as a reference and compared to the adolescent subjects using Z scores for all variables. Anthropometric characteristics and performances in physical fitness tests differed (p<0.05) among players of different sports. In addition, for each variable assessed, adolescents who practised team court sports showed similar or improved results compared to their counterparts in the general population (p<0.05). Furthermore, the anthropometric and physical fitness characteristics differed depending on the team court sport practised. These findings may elucidate which physical abilities are most impacted by the practise of a particular team sport as well as help teachers and physical education and sport professionals identify talented adolescents.